Impact of treatment time and waiting time on outcome for esophageal squamous cell carcinoma receiving definitive chemoradiotherapy - Geng Xiang; Xiaomeng Wang; Cong Zhang; Guangjin Chai; Bo Lyu; Yutian Yin; Bin Wang; Lina Zhao (Radiation Oncology)
Abstract Purpose To assess the effect of treatment time and waiting time on clinical outcome for patients with esophageal squamous cell carcinoma (ESCC) treated with definitive concurrent chemoradiotherapy (CCRT). Methods and materials A retrospective analysis was conducted on ESCC patients treated with definitive CCRT between 2008 and 2024 at Xijing hospital. Analyses were performed according to the following separate definitions of treatment time and waiting time: (1) theoretical minimal radiotherapy time (TMRT); (2) overall treatment time (OTT); (3) exceeding time (ET); (4) time to start of radiotherapy (TSR); (5) overall waiting time (OWT). Associations between treatment time and waiting time and survival outcome were investigated using Cox regression analyses. Results A total of 541 patients were studied and prolonged treatment time and waiting time were common. Overall, the median TMRT, OTT, ET, TSR, and OWT were 38 days [interquartile range (IQR): 38–40 days], 43 days (IQR: 40–47 days), 4 days (IQR: 2–7 days), 88 days (IQR: 62–126 days), and 21 days (IQR: 14–31 days), respectively. Multivariate analysis revealed that delay of treatment time and waiting time has no effect on overall survival (OS), locoregional relapse-free survival (LRFS), distant metastasis-free survival (DMFS), and progression-free survival (PFS) (all p > 0.05). In the subgroup of patients with T1-2 ESCC disease, the TSR < 72 days group had significantly more favorable OS (p = 0.009), LRFS (p = 0.003), and PFS (p = 0.022) compared with TSR ≥ 72 days group. Conclusions Delay of treatment time and waiting time has no effect on OS, LRFS, DMFS, and PFS. However, longer TSR was found to be associated with diminished survival outcomes for T1-2 stage rather than T3-4 ESCC patients treated with definitive CCRT.